Atypical brainstem representation of onset and formant structure of speech sounds in children with language-based learning problems - Wible, Brad; Nicol, Trent; Kraus, Nina (Biological psychology, 2004)
This study investigated how the human auditory brainstem represents constituent elements of speech sounds differently in children with language-based learning problems (LP, n=11) compared to normal children (NL, n=9), especially under stress of rapid stimulation. Children were chosen for this study based on performance on measures of reading and spelling and measures of syllable discrimination. In response to the onset of the speech sound /da/, wave V–V n of the auditory brainstem response (ABR) had a significantly shallower slope in LP children, suggesting longer duration and/or smaller amplitude. The amplitude of the frequency following response (FFR) was diminished in LP subjects over the 229–686 Hz range, which corresponds to the first formant of the/da/ stimulus, while activity at 114 Hz, representing the fundamental frequency of /da/, was no different between groups. Normal indicators of auditory peripheral integrity suggest a central, neural origin of these differences. These data suggest that poor representation of crucial components of speech sounds could contribute to difficulties with higher-level language processes.